WORKPLACE-BASED LEARNING IN THEORY AND DUAL SYSTEM OF PROFESSIONAL EDUCATION IN PRACTICE - Katane, Irena; Katans, Edgars; Īriste, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The ecological approach offers a wide range of opportunities regarding performing of interdisciplinary research in the educational sciences, as well as comprises significant potential of innovative, creative pedagogical activities in practice. One of the ways of the implementation of ecological approach is the workplace-based learning. The workplace-based learning are both scientific conception and strategy for the elaboration and development of professional education dual system in the state-level educational policy and educational management fields. The aim of research: to substantiate theoretically the workplace-based learning for the facilitation of the professional development of prospective and/or already working specialists. The concept of workplace-based learning has both wide and narrow meaning. According the wide meaning, the workplace-based learning facilitate the lifelong professional development of an individual for which the environment of professional activities is very important. According to the narrow meaning, the workplace-based learning mean the organization of prospective specialists' practice at the companies. The conception of workplace-based learning provides that the environment of professional education consists of two components: from the environment of educational establishment and from the base organization as the environment of professional activities. In the dual system of professional education both these environments form an indivisible integral entirety. The ecological approach provides a perspective for the sustainable development of dual professional education.